2014
DOI: 10.3904/kjim.2014.29.6.800
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of elderly chronic urticaria

Abstract: Background/AimsChronic urticaria (CU) is defined as itchy wheals lasting 6 weeks or more. As the aged population increases worldwide, it is essential to identify the specific features of this disease in the elderly population.MethodsWe investigated the prevalence and clinical features of CU in elderly patients. Medical records of 837 CU patients from the outpatient Allergy Clinic of Ajou University Hospital, Korea were analyzed retrospectively. Patients with chronic spontaneous urticaria according to the EAACI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
4
29
2
Order By: Relevance
“…This study indicates that approximately 25% of H1‐antihistamine‐refractory CSU patients have comorbid CIndU. Consistent with previous publications, other comorbidities in this patient population included asthma, allergic rhinitis, atopic dermatitis, allergies, and autoimmune diseases .…”
Section: Discussionsupporting
confidence: 90%
“…This study indicates that approximately 25% of H1‐antihistamine‐refractory CSU patients have comorbid CIndU. Consistent with previous publications, other comorbidities in this patient population included asthma, allergic rhinitis, atopic dermatitis, allergies, and autoimmune diseases .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, some studies showed that patients with CSU had significantly higher levels of IgG antithyroid AAbs compared to patients with acute and chronic inducible urticaria. The difference in IgG antithyroid AAb levels was not statistically significant when CSU patients with atopic diseases were compared to nonatopic CSU patients . However, another study showed higher rates of elevated IgG antithyroid AAbs in children with CSU and atopy …”
Section: Resultsmentioning
confidence: 85%
“…Ga-Young Ban et al 6 (N=37) 12.0 NA NA There were no statistically significant differences of the abnormal laboratory findings between both groups. However, aging patients with CU tended to have higher percentages of positive ASST, positive anti-thyroglobulin antibodies and positive anti-thyroid peroxidase antibodies in comparison with non-aging patients with CU.…”
Section: Table 4 Comparison Of Data Between Thai Aging Chronic Spontmentioning
confidence: 83%
“…Although there were sparse data focused on the clinical and laboratory characteristics of CSU in the aging population, data regarding CSU in 92 Israeli and 37 Korean geriatric patients have been reported by Magen et al and Ga-Young Ban et al, respectively. 5,6 We summarized and compared the data from their studies with ours, as shown in Table 4. The prevalence of CSU in aging Asian patients seemed to be lower than in aging Caucasian patients.…”
Section: Table 4 Comparison Of Data Between Thai Aging Chronic Spontmentioning
confidence: 99%
See 1 more Smart Citation